Peran Mahasiswa Dalam Meningkatkan Gotong Royong dan Kebersihan Lingkungan di Desa Japurabakti Kab.Cirebon - Fadhillah, Muhammad Daffa; Ulhaq, Dea Fitrianingka; Marina, Rina; Lidiawati, Ayi; Anwar, Saeful; Saumantri, Theguh (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2024)
Gotong royong has significant potential in addressing environmental cleanliness; however, this potential has not been fully realized due to a lack of community awareness regarding environmental cleanliness. Therefore, this research focuses on discussing the role of students in enhancing gotong royong and environmental cleanliness in Japurabakti Village. The gotong royong activities center on the role of KKN students in executing communal work. The involvement of KKN students in gotong royong is feasible given their scope of authority, and it is expected to build awareness about village cleanliness. Thus, effective strategies and policies are necessary for the successful implementation of these activities. The gotong royong activities aim to describe the role of the community in conducting gotong royong activities at Mushola An-Najikhin in Japurabakti Village. This community service project employs Participatory Action Research (PAR) methodology as a strategy to actively involve the community at every stage of implementation, from planning to execution and evaluation. The results of this activity show that gotong royong involving religious leaders and local community members can enhance the community's awareness of KKN students' roles in carrying out these activities. Additionally, the role of religious leaders as motivators also contributes to improving environmental cleanliness in Japurabakti Village